(3Jced eTGjN GHf fGLis - (3GHf fGLi bGSe Hf YjSi Hf fGLi GdJfhNi GdbjQhGfis; (3bGSe Hf YjSi Hf fGLj GdJfhNj GdbjQhGfj, GHf fGLj,J (B837 (3g` s ((3eMeO GdRefWi s)
(3ChdgG (B:s
(3CHh YHO Gddg eMeO Hf CHj jMji , HcQ GdaGSi GdePchQ QMeg Gddg JYGdi Hefg bQG Ydi TjNfG GdHjHi HGdbjQhGf s
(3BNQgG (B:s
(3hJhai CHh (B8(3YHO Gddg eMeO ai ChSW LeGOi GdChdi YGe KeJGfjI hKeGfeGFI hOaf HGdLHGfI GdZQHjI hbHQg eRGQ QegI Gddg Ydjg hQVhGf dOjg s
(3GdehLhO efg GdLRA GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs